Exporting, Skills and Wage Inequality - Moser, Christoph; Urban, Dieter; Klein, Michael W. (Labour Economics, 2013)
International trade has been cited as a source of widening wage inequality in industrial nations. Most previous empirical evidence supports this claim by showing an effect in which increasing exports tilt demand towards firms which export and employ a relatively large proportion of higher-skilled workers from the group of firms which do not export. We find that, in addition to this, there is also an effect whereby, among exporting firms, there is a significant wage premium for high-skilled workers and a wage discount for low-skilled workers. These estimates are based on a matched employer–employee data set of western German manufacturing firms over the period 1993–2007. Our estimates suggest that export activity can be associated with up to 30% of within and between skill group wage inequalit